“I wasn’t sure it would work. I was just trying”: an ethnographic study on the choice of abortion methods among young women in Kilifi County, Kenya, and Atlantique Department, Benin - Gladys Akinyi Omondi; Jonna Both; Ramatou Ouedraogo; Grace Kimemia; Kenneth Juma (Reproductive Health, 2023)
Abstract Background Despite the increased availability of safe abortion methods in sub-Saharan Africa, women and girls continue to use unsafe abortion methods and procedures to terminate their unwanted pregnancies, resulting in severe complications, lifelong disabilities, and death. Barriers to safe abortion methods include restrictive laws, low awareness of safe abortion methods, poverty, and sociocultural and health system barriers. Nonetheless, there is a paucity of data on the decision-making around and use of abortion methods. This paper aims to provide answers to the following questions: Which abortion methods do women and girls use and why? Who and what influences their decisions? What can we learn from their decision-making process to enhance the uptake of safe abortion methods? We focus our in-depth analysis on the rationale behind the choice of abortion methods used by women and girls in Kilifi County in Kenya and Atlantique Department in Benin. Methods We draw on data collected as part of an ethnographic study conducted between January and August 2021 on lived experiences, social determinants, and pathways to abortion. Data were collected using repeated in-depth interviews with 95 girls and women who had a recent abortion experience. Data from the interviews were supplemented using information from key informant interviews, focus group discussions, and participant observation. Data analysis was conducted through an inductive process. Results Our findings reveal that women and girls use various methods to procure abortions, including herbs, high doses of pharmaceutical drugs, homemade concoctions, medical abortion drugs, and surgical abortion methods. Procedures may involve singular or multiple attempts, and sometimes, mixing several methods to achieve the goal of pregnancy termination. The use of various abortion methods is mainly driven by the pursuit of social safety (preservation of secrecy and social relationships, avoidance of shame and stigmatization) instead of medical safety (which implies technical safety and quality). Conclusion Our findings reaffirm the need for comprehensive access to, and availability of, abortion-related information and services, especially safe abortion and post-abortion care services that emphasize both medical and social safety.